Circular RNAs in inflammatory bowel disease - Lun, Jie; Guo, Jing; Yu, Mengchao; Zhang, Hongwei; Fang, Jing (Frontiers in Immunology, 2023)
Inflammatory bowel disease (IBD) is a term encompassing a few chronic inflammatory disorders that leads to damage of the intestinal tract. Although much progress has been made in understanding the pathology of IBD, the precise pathogenesis is not completely understood. Circular RNAs (circRNAs) are single-stranded, covalently closed, endogenous molecules in eukaryotes with a variety of biological functions. CircRNAs have been shown to have regulatory effects in many diseases, such as cancer, cardiovascular disease, and neurological disorders. CircRNAs have also been found to play important roles in IBD, and although they are not sufficiently investigated in the context of IBD, a few circRNAs have been identified as potential biomarkers for the diagnosis and prognosis of IBD and as potential therapeutic targets for IBD. Herein, we survey recent progress in understanding the functions and roles of circRNAs in IBD and discuss their potential clinical applications.